EFFECT OF THAWINGLENGTH ON QUALITY OF BOAR SEMEN ATTECHNICAL SERVICE UNIT OF ARTIFICIAL INSEMINATION CENTRE BALI PROVINCE - Y. N. S., Simarmata; Sumardani, N. L. G.; ArtiningsihRasna, N. M. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
The aims of this research was toknow the effect of thawing length on the quality of boar semen at Technical Service Unit (TSU) of Artificial Insemination Centre (AIC), Bali Province.The research was conducted for two months (April– May, 2018)in two different placeswereTSUof AIC Baturiti District,Tabanan and TSU ofAIC Buruan District,Gianyar-Bali.The material used were two landrace(2 years old) at TSU of AICBaturiti and the other two landrace (2 years old) at TSU of AIC Buruan. The researchused design Completely Randomized Design (CRD) with 3 treatmentswere the first treatment (T1) was 3 minutesthawing length, the second treatment (T2)was5 minutes thawing length and the third treatmentwas 7 minutes thawing length,and each treatment consisted of 5 replications. Variables observed were volume, color, odor, consistency, pH, motility, concentration and viability.Results of the researchshowed that the T1, T2, and T3 were no change on volume, color, smell, and consistency.Whereas pH, motility, concentration and viability were significantdifference (P<0.05) within the treatmentT1, T2 and T3.It could be concluded that 5 minutes thawing length at TSU of AIC Baturiti was the best, while at TSU of AIC Buruan it was 3 minutes. Keywords: thawing, semen, Landrace, quality